Employee Engagement, Work-Life Balance, and Workforce Productivity: Evidence from Indonesian Manufacturing Employees - Sabina Mutiara; Erina Rulianti (Lentera Ilmu Nusantara, 2026)
This study aims to analyze the influence of employee engagement and work-life balance on employee productivity in manufacturing companies in Indonesia. The manufacturing industry faces complex challenges in the era of digital transformation and intensive global competition, where employee productivity becomes a crucial determinant for company sustainability. The characteristics of the manufacturing industry with repetitive work, high production targets, and long working hours create particular challenges in maintaining optimal employee engagement and work-life balance. This study employs a quantitative approach with a survey method through questionnaires distributed to 76 employees in the production department of manufacturing companies. The sampling technique uses the Slovin formula with a 5% error rate. Employee engagement measurement utilizes three dimensions: emotional, cognitive, and physical involvement, while work-life balance is measured through time balance, involvement balance, and satisfaction balance. Work productivity is measured through indicators of capability, work result improvement, work enthusiasm, self-development, quality, and efficiency. The analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Square (PLS), and multiple regression analysis. This research is expected to provide theoretical contributions through the development of a contextual integrative model for the Indonesian manufacturing industry, as well as practical implications for management in designing sustainable, humanistic productivity improvement strategies that are adaptive to contemporary employee needs, particularly millennials and Gen Z who dominate the workforce.